The Implementation of Halal Tourism Ecosystem Model in Borobudur Temple as Tourism Area - Sutono, Anang; Tahir, Shaharuddin; Sumaryadi, Sumaryadi; Hernowo, Andre; Rahtomo, Wisnu (UIN Sunan Gunung Djati Bandung, 2021)
Borobudur as one of the top wonderful destinations in the world is challenged to become one of halal tourism destinations in Indonesia. The purposes of this research are to find out and to launch the implementation of halaltourism ecosystem model in Borobudur Temple as tourism area in Indonesia. This research used a descriptive method. The researcher investigated the implementation of halal tourism ecosystem model in the Borobudur temple as tourism area by examining the variables of halal tourism ecosystems. It consisted of four dimensions. They are destination products, government support, human resources, and infrastructure. The main data is collected by using interviews and addressing of Borobudur Temple Tourism Park management, Tourism Business People that concerned with halal certification, LPPT (Integrated Research and Testing Laboratory) University of Gajah Mada, Indonesian Ulama chapter Jogjakarta, Culture and Tourism Region of Jogjakarta. The tools of data collection are the checklist and literature study to grab the secondary data. The result shows that Halal Tourism destination product, including the availability of halal attraction, facility, accessibility, program, and the package are not available completely. However, the support aspect from the government is not optimal in supporting Borobudur as halal tourism destination. Based on human resources aspect, there is founded that in some aspects such as the availability of human resources that understand of tourism is very poor or almost none. Besides, based on infrastructure aspect, there is founded that research and development aspects have not been carried out optimally.